1999
DOI: 10.1177/004947559902900205
|View full text |Cite
|
Sign up to set email alerts
|

Active Prophylactic Management of Respiratory Obstruction after Standard Thyroidectomy for Giant Goitre in the Middle Belt Region of Nigeria

Abstract: Respiratory obstruction is a lethal complication of thyroidectomy for giant goitre. Prophylactic tracheal splintage by retaining the endotracheal tube in situ for 24 h post-operatively and its meticulous management in the intensive care unit (ICU) is a safe and rewarding practice. Over a 7-year period, 33 patients, all women who had standard thyroidectomy for giant goitre were managed accordingly. There was no incidence of post-operative respiratory distress, nor mortality in the series. The average duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This further supports the findings of Olurin et al who reported that the skill of thyroidectomy improved so much over the years that the incidence of postthyroidectomy tracheostomy fell from 25% to less than 3% over all. 6 In a recent report, Obekpa et al 7 reported a series of 33 patients with large or giant goitres who had prophylactic tracheal splintage by retaining the endotracheal tube in-situ for 24h. postoperatively in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…This further supports the findings of Olurin et al who reported that the skill of thyroidectomy improved so much over the years that the incidence of postthyroidectomy tracheostomy fell from 25% to less than 3% over all. 6 In a recent report, Obekpa et al 7 reported a series of 33 patients with large or giant goitres who had prophylactic tracheal splintage by retaining the endotracheal tube in-situ for 24h. postoperatively in the ICU.…”
Section: Discussionmentioning
confidence: 99%